System Dynamics for Mechanical Engineers - Davies, Matthew; Schmitz, Tony L. (Springer New York : Imprint: Springer, 2015)
This textbook is ideal for mechanical engineering students preparing to enter the workforce during a time of rapidly accelerating technology, where they will be challenged to join interdisciplinary teams. It explains system dynamics using analogies familiar to the mechanical engineer while introducing new content in an intuitive fashion. The fundamentals provided in this book prepare the mechanical engineer to adapt to continuous technological advances with topics outside traditional mechanical engineering curricula by preparing them to apply basic principles and established approaches to new problems. This book also: ·         Reinforces the connection between the subject matter and engineering reality ·         Includes an instructor pack with the online publication that describes in-class experiments with minimal preparation requirements ·         Provides content dedicated to the modeling of modern interdisciplinary technological subjects, including opto-mechanical systems, high-speed manufacturing equipment, and measurement systems ·         Incorporates MATLAB® programming examples throughout the text ·         Incorporates MATLAB® examples that animate the dynamics of systems.